Comparison of Different Techniques for Early Pregnancy Diagnosis in Surti Does - Parmar, Chirag P; Patel, Jagdish A; Islam, Md Manzarul; Pathan, Mohsinkhan M; Madhira, Suryaprakash P; Patel, Dignesh K (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
Thirty adult Surti goats which did not return to estrus after service by normal fertile bucks at induced estrus following different synchronization protocols were selected for early pregnancy diagnosis by three different techniques, viz., serum progesterone levels on day 22, pregnancy associated glycoprotein (PAG) levels on day 22 and 26, and transabdominal ultrasonography (USG) on day 35 after breeding. The does were considered positive when the concentration of serum progesterone was over 1.0 ng/mL and PAG over 1.5 ng/mL. The mean serum progesterone levels on day 22 after breeding in goats diagnosed pregnant correct, pregnant incorrect and not-pregnant correct were 7.38±0.33, 5.00±0.00 and 0.65±0.00 ng/mL, respectively. The levels of PAG (ng/mL) in diagnosis pregnant correct and non-pregnant correct on day 22 and 26 were 3.09±0.06 and 0.54±0.5; 19.03±0.25 and 0.43±0.02, respectively. The mean level of serum PAG on day 22 in diagnosis not-pregnant incorrect was found to be 0.99±0.03 ng/mL. Out of 30 goats, 26 goats were found pregnant based on observations of foetus and heartbeats during ultrasonography on day 35, but kidding occurred in 28 does. The sensitivity, specificity, +ve predictive value, -ve predictive value and diagnostic accuracy of early pregnancy diagnosis by progesterone assay on day 22 were 100.00, 50.00, 96.55, 100.00 and 96.66 %, respectively. The corresponding percentages for PAG on day 22 were 92.86, 100.00, 100.00, 50.00 and 93.33, respectively. However, all these parameters were found 100 % on day 26. The percentage values of above parameters of USG for early pregnancy diagnosis on day 35 were 92.86, 100.00, 100.00, 50.00 and 93.33 %, respectively. It was concluded that the earliest pregnancy diagnosis can be done by estimation of PAG on day 26 with cent per cent accuracy. However, looking to the Indian goat owners’ economic condition, ultrasonography is quick and safe for early pregnancy diagnosis.